Analisis Potensi Pengembangan Pembangkit Listrik Tenaga Mikrohidro Di Kabupaten Bone Bolango - Nurhayati Doda; Herdi Mohammad (Universitas Gorontalo, 2018)
Energy is a major need in human life, but along with the population growth will be the availability of electrical energy especially that from fossil fuels are being reduced and insufficient for the needs of small-scale electric power listrik.Pembangkit potential as an alternative to fossil energy sources namely renewable micro hydro power plant availability of electricity in remote villages in the district of Bone Bolango is alarming, so it was done research on Analysis of Potential Development of micro hydro power plant (MHP) in Bone regency Bolango. This study aims to provide an overview and preliminary information on the potential of hydropower as a basis for planning and development of micro hydro power plant. In this research will be outlined potential sites for the development of MHP with power potential, specifications turbindan civilian buildings. Measurement of power was awakened by the amount of streamflow in Mongiilo Desa Ulu Subdistrict Bolango Bone Bolango District. Debit analyzed based on observation of the flow rate by using a current meter. From the analysis of the amount of power potential in getting aroused in the research area of 289,935Kw with ideal flow 12.14 m3 / sec, the average efficiency of 65% with the plan fell 3.75 m high. This power is sufficient magnitude elektrifitas needs of residents in the study area that is equal to 65kW.